The Decollement Depth of Active Thrust Faults in Italy: Implications on Potential Earthquake Magnitude. Issue 11 (21st November 2019) - Petricca, P.; Carminati, E.; Doglioni, C.
Abstract: Thrust fault ruptures during earthquakes do not often propagate down to the brittle‐ductile transition. Lithological variations control the behavior and depth of regional basal thrusts and decollement planes. Thrust fronts may be discontinuous along strike, limiting the dimension of single coseismic ruptures. These factors control the maximum expected magnitude in one region. This is the case of Italy where the convergence of few millimeter per year in the Apennines accretionary prism and along the retrobelt of the Alps generates compressional earthquakes with moderate to strong magnitudes. Here, using geological and geophysical data, we first compile a map of the undulated active basal thrust decollement for Italy that occurs from 1 to 17‐km depth. Then, we verify the relationship between the length of seismogenic ruptures in thrust faults (Lf) and the maximum depth of thrust faulting (zmax ) of related earthquakes and find that their ratio (Lf/zmax ) ranges between 2 and 4. Finally, we compute the potential seismogenic volume and estimate the maximum magnitude using an empirical relationship that multiplies the decollement depth and the Lf/zmax ratio. Maximum calculated magnitude is 6.7 ± 0.37 (depending on Lf/zmax and fault dip angle), consistent with the largest magnitude of thrust‐related earthquakes recorded in Italy (6.5–7.0). Lower magnitudes are predicted in the Ionian Seas at the external front of the Apennines where smaller crustal volumes are involved, whereas higher magnitudes are expected in the southern Po Basin, the western Adriatic Sea, Sicily offshore, and the Southern Alps where the decollement is deeper and the brittle volumes are far greater. Plain Language Summary: Earthquakes are due to different kinds of crustal fault ruptures, and the observed magnitude depends on the rupture dimension, hence on the involved brittle volume. Those related to thrust faults generate magnitudes lower than expected if the decollement is shallow, whereas the magnitudes increase where the decollement is deeper. This is the case of Italy where many factors can explain the moderate to strong (M 5–7) observed magnitudes recorded so far in the contractional areas of the country: (i) the slow convergence rate (few millimeters per year) observed for the Apennines and Alps; (ii) the thrusts do not cut down the entire seismogenic crust; and that (iii) thrusts are undulated and segmented along strike, limiting the dimension of the fault rupture. We compile a map of the thrust decollement depth for Italy that is situated between 1–17 km. Then, we quantify the along‐strike discontinuity, verifying the ratio between thrusts length and faulting depth of related earthquakes. Finally, we estimate the maximum expected magnitude for the study area. Calculated magnitudes are consistent with those occurred for thrust‐related earthquakes in Italy, pointing to the importance of knowing the depth and the lateral continuity of faults to correctly assess the seismic potential of a region. Key Points: The basal active thrust decollement is mapped on the Italian accretionary prisms We define the relationship between the length of thrusts ruptures and maximum faulting depth (Lf/zmax ) for Italian earthquakes Seismic volumes calculated from faulting depth and Lf/zmax ratio provide a good estimation of expected magnitudes